High Humidity Alters Myeloid-Derived Suppressor Cells in Spleen Tissue: Insights into Rheumatoid Arthritis Progression - Wang H; Wang M; Wang T; Li X; Wen C; He Z; Huang L (Journal of Inflammation Research)
Hongli Wang,1,2,* Mingzhu Wang,1,2,* Tengyue Wang,1,2 Xuanlin Li,1,2 Chengping Wen,1,2 Zhexing He,1,2 Lin Huang1,2 1Research Institute of Chinese Medical Clinical Foundation and Immunology, School of Basic Medical Science, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China; 2Key Laboratory of Chinese Medicine Rheumatology of Zhejiang Province, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Huang; Zhexing He, College of Basic Medical Science, Zhejiang Chinese Medical University, 548 Binwen Road, Binjiang District, Hangzhou, People’s Republic of China, Email huanglin@zcmu.edu.cn; hzx2015@zcmu.edu.cnBackground: Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation and bone destruction, leading to severe complications. Previous research has suggested that high humidity conditions may exacerbate RA, however, the underlying mechanisms remain unclear. Furthermore, there is a lack of evidence linking humidity to the worsening of RA symptoms in animal models.Methods: The Collagen-induced arthritis (CIA) mouse model was established using C57BL/6 mice. The arthritis status of the mice was evaluated under two distinct humidity conditions (50% and 80%). The aim of the present study was to investigate the impact of elevated humidity levels on the types of splenic cells present using mass spectrometry flow. Additionally, the study utilized MDSCs, which are significantly upregulated by high humidity, to assess the levels of oxidative stress and conducted mRNA sequencing of sorted MDSCs to investigate their impact on arthritis in CIA mice.Results: Compared to normal humidity, high humidity exacerbated arthritis incidence in mice, resulting in increased arthritis scores, swelling, serum autoantibodies (anti-COII and anti-CCP), and upregulation of pro-inflammatory cytokines. Significant variations were observed in the spleen index under high humidity condition, accompanied by noticeable inflammatory alterations. Moreover, elevated humidity levels induced a substantial modulation in MDSCs population in the spleen of CIA mice, along with alterations in oxidative stress markers such as heightened serum ROS levels, and increased expression of COX, SOD, and Nrf2 mRNA. Following successful sorting of MDSCs, mRNA sequencing revealed a decrease in the expression of Rap1 signaling pathway under high humidity environment, which may contribute to the increase of MDSCs cells and aggravate the progression of RA disease.Conclusion: A comprehensive analysis of the available data reveals a detrimental impact of high humidity on MDSCs numbers within spleen tissue, with potential implications for the development of RA.Keywords: rheumatoid arthritis, high humidity environment, myeloid-derived suppressor cells, Rap1 signaling pathway